2009
DOI: 10.1038/ejcn.2009.93
|View full text |Cite
|
Sign up to set email alerts
|

Is the association of type II diabetes with waist circumference or waist-to-hip ratio stronger than that with body mass index?

Abstract: In total, 17 prospective and 35 cross-sectional studies in adults aged 18-74 years, with the aim of comparing betweenbody mass index (BMI), waist circumference (WC) and waist-to-hip ratio (WHR) in their relation to the incidence and prevalence of type II diabetes, were reviewed. Among these studies, only a few have used C-statistic, paired homogeneity test or log-likelihood ratio test for formally comparing the differences. Five prospective studies, in which formal statistic tests have been made, came out with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
112
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(124 citation statements)
references
References 58 publications
7
112
0
3
Order By: Relevance
“…This has been clearly demonstrated in the general population using BMI, waist circumference, and waist-hip ratio as markers for weight (25,26). Also in this study, diabetic patients showed a significantly higher BMI and waist circumference than the nondiabetic patients.…”
Section: Discussionmentioning
confidence: 59%
“…This has been clearly demonstrated in the general population using BMI, waist circumference, and waist-hip ratio as markers for weight (25,26). Also in this study, diabetic patients showed a significantly higher BMI and waist circumference than the nondiabetic patients.…”
Section: Discussionmentioning
confidence: 59%
“…In a metaanalysis of 32 prospective studies, BMI, waist circumference and WHR had associations with incident type 2 diabetes that were not significantly different [17]. In a review examining variation in the c-statistic (17 prospective studies, 35 cross-sectional studies), Qiao and Nyamdorj found that no measure had consistently higher explanatory power for type 2 diabetes risk [18]. In our study, BMI, waist circumference and WHR had nearly identical associations with type 2 diabetes and AUC OGTT, and similar explanatory power.…”
Section: Resultsmentioning
confidence: 98%
“…Data were inconclusive or insufficient to come to conclusions that special cutoff points would be required for any of the other ethnic groups addressed in the reviews. Qiao and Nyamdorj (2009a) also review data from a diverse set of populations on several continents, and address the issue of ethnicity or population-specific cutoff points, using the risk of type II diabetes as a reference point for evaluating optimal cutoff points. Their review finds evidence of substantial variations in the WC or WHR cutoff points that might be optimal in different countries or regions.…”
Section: Background Reviewsmentioning
confidence: 99%